Coral reef-associated brachyuran fauna (Crustacea: Decapoda: Brachyura) from Angria Bank off the west coast of India - Padate, Vinay P.; Periasamy, Rengaiyan; Rivonker, Chandrashekher U.; Ingole, Baban S. (Zootaxa, 2023)
Underwater sampling via SCUBA and grab at the Angria Bank coral reefs off the central west coast of India in January 2014 revealed 11 species of Brachyura. Seven species, namely, Thusaenys irami (Laurie, 1906), Tanaocheles bidentata (Nobili, 1901), Portunus convexus De Haan, 1835, Xiphonectes macrophthalmus (Rathbun, 1906), Thalamita gatavakensis Nobili, 1906, Serenius ceylonicus (Laurie, 1906), and Soliella flava (Rathbun, 1894) are reported for the first time from Indian waters. Furthermore, the geographical distribution of T. irami and S. ceylonicus is extended westwards of hitherto known ranges.